Physiological responses of pedunculate oak (Quercus robur L.) to Corythucha arcuata (Say, 1832) attack - Nikolić, Nataša; Pilipović, Andrej; Drekić, Milan; Kojić, Danijela; Poljaković-Pajnik, Leopold; Orlović, Saša; Arsenov, Danijela (Archives of Biological Sciences, 2019)
Paper description: Herbivory insects can affect photosynthetic characteristics, foliar nutrients and the oxidative status of plant tissues in different host species. To our knowledge, this is the first report on the effect of oak lace bug (Corythucha arcuate) feeding on the photosynthetic characteristics and gas-exchange parameters, mineral nutrient concentrations and potential defense mechanisms (activities of some antioxidant enzymes) on the leaves of Quercus roburL. (pedunculate oak). Elucidation of the physiological responses should contribute to an improved understanding of the mechanisms involved in the response of host plants to stress induced by insect herbivory. Abstract: The spread and occurrence of the oak lace bug Corythucha arcuata out of its natural distribution area across European and Asian countries has been reported during the past decades. The ecological and economic significance of oak stands and the vulnerability of plants to various abiotic and/or biotic factors requires in-depth knowledge of plant-pest interaction. The present study examined the influence of C. arcuata feeding on the photosynthetic characteristics and gas-exchange parameters, mineral nutrient concentrations and defense mechanisms (the activities of some antioxidant enzymes) of leaves of pedunculate oak. The rate of photosynthesis, transpiration and stomatal conductance were lowered by 58.84, 21.66 and 35.71%, respectively, in comparison to non-infested plants. The concentrations of photosynthetic pigments and activities of antioxidant enzymes, catalase and ascorbate peroxidase, were affected by the presence of C. arcuata. To our knowledge this is the first paper providing a report on the physiological responses of Quercus robur plants exposed to C. arcuata infestation. Understanding the impact of pests, such as the invasive species C. arcuata on physiological processes and vitality of young plants and plant responses, could provide a foundation for efficient preservation of oak forests endangered by the oak lace bug. https://doi.org/10.2298/ABS180927058N Received: September 27, 2018; Revised: November 30, 2018; Accepted: December 14, 2018; Published online: December 26, 2018 How to cite this article: Nikolić N, Pilipović A, Drekić M, Kojić D, Poljaković-Pajnik L, Orlović S, Arsenov D. Physiological responses of Pedunculate oak (Quercus robur L.) to Corythucha arcuata (Say, 1832) attack. Arch Biol Sci. 2019;71(1):167-76.